Reduction of Aldehydes Using Sodium Borohydride under Ultrasonic Irradiation - Maulidan Firdaus; Nestri Handayani; Lina Tri Marfu’ah (Indonesian Journal of Chemistry, 2016)
A simple, energy efficient, and relatively quick synthetic procedure for the reduction of aldehydes under ultrasonic irradiation is reported. Satisfactorily isolated yields (71-96%) were achieved confirming that the preparation of alcohol by aldehyde reduction is possible in green and sustainable fashion.